Using the whole language approach to teaching Mandarin speaking skills in Indonesia - Tri Budianingsih (Jurnal Magister Ilmu Hukum, 2018)
Abstrak-The major purpose of teaching methods is to achieve the abilities and knowkedge that the teachers want for their students. Teaching that involves listening and speaking skills aims to assist students express differences of pronunciation and understand meaning. The pronunciation should be precise, should be in an appropriate tone and the word used to express the idea must be appropriate. The focus of this qualitative research project is focused on the process of teaching speaking Mandarin in the classroom using the whole language approach. Data collection procedures involved observations by the researchers and searching the literature for books.Keynote: Using Language, Teaching Mandarin, Speaking